PENINGKATAN KINERJA GURU MELALUI SUPERVISI EDUKATIF KOLABORATIF SECARA PERIODIK DI SMK MUHAMADIYAH 1 BERBEK NGANJUK TAHUN PELAJARAN 2014/2015 - Zainal Aqib (STIT Muhammadiyah Paciran Lamongan, 2019)
The aim of this study wanted to describe the steps educative collaborative supervision periodically in preparing lesson plans, implement lessons, assessing student achievement, conduct follow - up assessments student achievement that can improve the performance of teachers. This performance improvement through collaborative educative periodic supervision. This research was conducted on teachers SMKM 1 Berbek Nganjuk totaling 10 people. Research actions implemented starting in January until March 20 14 . The design of the study is that the plot action research design: make a action plain, implementing the action, and reflection activities. The reflection is used as a guide for decision - making to continue or discontinue the study. Researc h conducted in the spiral cycles to the second cycle. The research data in the form of records of observations, field notes, documentation planning and supervision results. The main data collection instrument was a researcher, while the supporting instrume nts is the observation, documentation. Data were analyzed by qualitative and quantitative techniques. Based on the results of the action research can be concluded that the improved performance of teachers in preparing lesson plans, implement lessons, asses sing student achievement, conduct follow - up assessments of student learning achievement. To that end, the researchers suggested that educative supervision in schools implement collaborative educative periodic supervision.